Zehn Jahre junge Kunst in Malmö : Zwischen 80 - 90. - Kampnagelfabrik, Hamburg; Konsthall, Malmö (Hamburg : Kampnagelfabrik, 1991)
Anders A ; Billgren, Ernst ; Billgren, Ola ; Dawid ; Ekholm, Lars ; Forslund, Leonard ; Hydén, Acke ; Ingvarsson, Jarl ; Jacobson, John ; Johansson, Michael ; Kappel, Anders ; Löfdahl, Eva ; Nilsson, Lars ; Persson, P.O. ; Sjölund, Stig ; Svenbro, Annika ; Albrecht, Jürgen ; Anger, Renate ; Balkenhol, Stephan ; Betke, Wolfgang ; Blumenthal, Heiner ; Brillowska, Mariola ; Deistler, Michael ; Kluge, Gustav ; Kumrow, Klaus ; Nieslony, Boris ; Prinz, Bernhard ; Rahayel, Claudia ; Eun Nim Ro ; Rose, Rolf ; von Stockhausen, Friedemann
Zehn Jahre junge Kunst in Malmö : Zwischen 80 - 90, Kampnagelfabrik, Hamburg, 9/2 - 3/3.1991 ; Konstmuseet Malmö, 27/1 - 24/2.1991
boek
Keywords: Hamburg; Malmö